1986
DOI: 10.1002/stem.5530040601
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecule‐cell interactions and the regulation of myelopoiesis

Abstract: The regulation of myelopoiesis in vivo most likely entails a complex set of interactions between cell-derived biomolecules and their target cells. Much of what we currently know of these interactions has been derived from studies in vitro utilizing techniques for the purification of both the biomolecules and the cells producing and responding to these factors. Stimulating and suppressing influences have been uncovered, and with the cloning and purification of biologically active factors, studies assessing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
47
0
1

Year Published

1987
1987
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 225 publications
(49 reference statements)
0
47
0
1
Order By: Relevance
“…Given its presence in exocrine glands and the secondary granules of neutrophilic leukocytes, lactoferrin is found in many body fluids, including milk, saliva, tears, bile, and pancreatic fluid (2). To date, lactoferrin has been shown to be involved in a variety of biological functions such as cell growth and differentiation (3)(4)(5), modulation of the inflammatory response (6), antiviral effects (7), and the regulation of myelopoiesis (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Given its presence in exocrine glands and the secondary granules of neutrophilic leukocytes, lactoferrin is found in many body fluids, including milk, saliva, tears, bile, and pancreatic fluid (2). To date, lactoferrin has been shown to be involved in a variety of biological functions such as cell growth and differentiation (3)(4)(5), modulation of the inflammatory response (6), antiviral effects (7), and the regulation of myelopoiesis (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Myeloid blood cell production is regulated by networks of cell interactions involving production and release from accessory cells of molecules such as the hematopoietic colony-stimulating factors (CSFs): multi-CSF [also termed interleukin 3 (IL-3)], granulocyte-macrophage (GM)-CSF, granulocyte (G)-CSF, macrophage-CSF, as well as erythropoietin (Epo), and interleukins 1-6 (3)(4)(5)40). Activin and inhibin, which, respectively, enhance and suppress release of follicle-stimulating hormone from pituitary cells in vitro (6)(7)(8)(9), have been shown to influence erythroid cells in vitro (10)(11)(12).…”
mentioning
confidence: 99%
“…9,10) To date, it has been reported that LF is involved in a variety of biological functions, such as cell growth and differentiation, [11][12][13] modulation of the inflammatory response, 14) anti-viral effects, 15) and regulation of myelopoiesis. 16,17) LF showed inhibitory effects on PLT aggregation by binding to the LF receptor which exists on the surface of PLTs, 5) but it is unclear whether LF can act on MKs though the LF receptor on the MKs. 6) Therefore, we assume that LF may contribute to differentiation of MKs as well as being involved in cell proliferation and differentiation.…”
mentioning
confidence: 99%